Coping and growing in dilemma: Clinical work experience of front‐line nurses in Wuhan during the early stage of COVID‐19 epidemic. Issue 4 (11th May 2021) - Xu, Fen; Tang, Ju‐ping; Lu, Sha; Fang, Hong‐wei; Dong, Lili; Zhou, Yun‐xian
Abstract: Aim: To deeply explore the experience of front‐line nurses who participated in rescuing Wuhan during the early stage of coronavirus disease 2019 (COVID‐19) epidemic. Methods: Using a descriptive qualitative design, individual semi‐structured interviews were conducted between February 25 and March 5, 2020. A conventional content analysis method was used in data analysis to extract themes and sub‐themes. Results: Six themes emerged after data analysis: (a) worries and stress during rescue; (b) difficulties encountered during rescue; (c) experience of team work; (d) experience of interaction with COVID‐19 patients; (e) experience of logistic support and widespread concern; and (f) value and significance of the experience. Conclusions: Nurses took on difficult missions in the rescue and played an irreplaceable role. They experienced remarkable psychological changes over the intensive work. It was necessary to understand the feelings and problems of the nurses so as to establish a healthcare system that can protect medical staff effectively in future disasters.